Realtime control and monitoring aquaponic system via Blynk / Wan Ahmad Firdaus Wan Azhar ... [et al.] - Wan Azhar, Wan Ahmad Firdaus; Md Kamal, Mahanijah; Ismail Khan, Zuhani; Othman, Kama Azura (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This work helps to control and monitor the aquaponic system in real-time. Aquaponic is a combination of hydroponic and aquaculture where in this work it is the integration of basil and Puyu fish. Normally, the activities such as checking the temperature, humidity and pH level of the aquaponic system is done manually. Therefore, the aims of this work is to develop a real-time control and monitoring system that can operates wireless via Blynk application. This aquaponic system consists of Puyu Fish or known as anabas testudineus with the hydroponic basil plant based on the seeds and stem cutting techniques. This hardware was built based on Arduino mega as controller, DHT11 sensor, and esp8266 wifi module. The blynk application through a smart phone is used to display the temperature and humidity of the aquaponics system. If the high temperature higher than the setting value of 30°C, it will quickly notify the user to take appropriate action. From the result obtained it shows that the pH level of basil is between 6.48 - 6.68 using seed technique and 6.71 - 6.88 through stem cutting.